1996
DOI: 10.1074/jbc.271.45.28038
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Characterizations of Yeast Guanylate Kinase

Abstract: Yeast guanylate kinase was expressed at high level in Escherichia coli using pET-17b vector. It was purified to homogeneity by a simple two-column procedure with an average yield of ϳ100 mg/liter. The steady-state kinetic parameters for both forward and reverse reactions were determined by initial velocity measurements. The turnover numbers (k cat ) were 394 s ؊1 for the forward reaction (formation of ADP and GDP) and 90 s ؊1 for the reverse reaction (formation of ATP and GMP). K m values were 0.20, 0.091, 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 33 publications
6
75
0
3
Order By: Relevance
“…1A and Table I), which is similar to that reported by others (39). We also evaluated GK activity and found that YGK was active with a K m of ϳ40 M, but that neither PSD-95-SH3GK nor CASK-SH3GK showed catalytic activity (Fig.…”
Section: Resultssupporting
confidence: 74%
“…1A and Table I), which is similar to that reported by others (39). We also evaluated GK activity and found that YGK was active with a K m of ϳ40 M, but that neither PSD-95-SH3GK nor CASK-SH3GK showed catalytic activity (Fig.…”
Section: Resultssupporting
confidence: 74%
“…In all cases, GTP reversed inhibition by excess UMP. Because inhibition by excess nucleoside monophosphate has also been observed with other NMP kinases such as E. coli adenylate kinase (25,26) and CMP kinase (27) and yeast GMP kinase (28), several common causes might be invoked to explain this phenomenon. Binding of UMP to the MgATP site is excluded, as inhibition is not competitive with MgATP.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these limitations, we found that at low concentrations (2 M GDP, 10 M GMPK), no complex with GTP was formed within the first 10 min and complexes of GMPK⅐GDP (22,448) were almost exclusively detected. The formation of GMPK⅐GTP (22,528) correlated with the formation of GMPK⅐GDP 2 (22,891).…”
Section: Resultsmentioning
confidence: 99%
“…All these findings can be explained with a simple modification of the commonly employed reaction scheme (22).…”
Section: Resultsmentioning
confidence: 99%